Automation for digital forensics: towards a definition for the community - Michelet, Gaëtan; Breitinger, Frank; Horsman, Graeme (Elsevier, 2023)
With the increasing amount of digital evidence per case, the automation of investigative tasks is of utmost importance to the digital forensics community. Consequently, tools are published, frameworks are released, and artificial intelligence is explored. However, as the foundation, i.e., a definition, classification, and common terminology, is missing, this resembles the wild west: some consider keyword searches or file carving as automation while others do not. We, therefore, reviewed automation literature (in the domain of digital forensics as well as other domains), performed three practitioner interviews, and discussed the topic with domain experts from academia. On this basis, we propose a definition and then showcase several considerations with respect to automation for digital forensics, e.g., what we classify as no/basic automation as well as full automation (autonomous). We conclude that it requires these foundational discussions to promote and progress the discipline through a common understanding.
Keywords: Automation; Definition; Practitioner interviews; Digital Forensic investigation; Investigative task